Lyme Neuroborreliosis: Preliminary Results from an Urban Referral Center Employing Strict CDC Criteria for Case Selection - David S. Younger; Stuart Orsher (Neurology Research International)
Lyme neuroborreliosis or “neurological Lyme disease” was evidenced in 2 of 23 patients submitted to strict criteria for case selection of the Centers for Disease Control and Prevention employing a two-tier test to detect antibodies to Borrelia burgdorferi at a single institution. One patient had symptomatic polyradiculoneuritis, dysautonomia, and serological evidence of early infection; and another had symptomatic small fiber sensory neuropathy, distal polyneuropathy, dysautonomia, and serological evidence of late infection. In the remaining patients symptoms initially ascribed to Lyme disease were probably unrelated to B. burgdorferi infection. Our findings suggest early susceptibility and protracted involvement of the nervous system most likely due to the immunological effects of B. burgdorferi infection, although the exact mechanisms remain uncertain.